The Waveshaper Effect on Ta-MS Multiliner Explosive Formed Pojectile with Tantalum as Penetrator and Mild Steel as Stabilization Base - Ghulam, Hussain; Abdul Qadeer, Malik; Khairuddin, Sanaullah (School of Chemical & Materials Engineering, National University of Sciences & Technology, Islamabad, Pakistan., 2011)
Numerical simulation was carried out using Autodyn 2D code to study the formation and tandem behavior of multiliner EFPs (Explosively Formed Projectiles). The main aim of multiliner configuration is to develop tandem behavior and to increase the length of explosively formed projectile in different applications. The high ductility and high dynamic material behavior of Ta (Tantalum) makes it difficult to generate a solid and stable projectile. To get these specific characteristics, mild steel was used for being the most stable liner material in the EFP technology. So when we used mild steel as a stabilization base and tantalum as a penetrator then solid and stable projectile was achieved. The tandem behavior with tantalum-mild steel multiliner configuration was studied. The effects of detonation method, confinement and waveshaper on the multiliner EFP configuration have also been determined by simulation. The detonation method has its effect on the tandem behavior whereas confinement has not. The waveshaper is found to have 40.4% more prominent and faster tandem effect on the multiliner EFPs.